Redesigning the University of the Future (UotF) through humanizing education and industry revolution 4.0 - Nasution, Ammar Ihsan; Ahmad Dahlan, Abdul Rahman; Ibrahim, Jamaludin; Mohd Alwi, Norhayati (Research Publish Journals, 2018)
Globalization and industry revolution IR 4.0 affect all aspects of life. Traditional letter rarely used by the current society. As the impact of IR 4.0, society nowadays rely and use internet as the media of communication. People also prefer to read from online news compare to traditional newspaper. Online shopping also become new trends and routine of the society. IR4.0 also affects education sector. E-Learning, smart board, E-book, E-library are some of the new technology that entered the education sector. As technology rise significantly, the higher education institution should take this as challenge and opportunity to prepare better education for the future of nation. When it comes to better education, the graduated student must be equipped with good knowledge and morality as well. To ensure this happen, humanizing education become another important aspect to be implemented in the future university. Thus, this paper research and proposed the conceptual solution to realize university of the Future by harnessing digital transformation and humanizing education.